Disparities and outcomes of patients living with Down Syndrome undergoing healthcare transitions from pediatric to adult care: A scoping review. Issue 8 (10th June 2022) - Varshney, Karan; Iriowen, Rosemary; Morrell, Kayla; Pillay, Preshon; Fossi, Alexander; Stephens, Mary M.
Abstract: Down Syndrome (DS) is one of the most common chromosomal disorders worldwide, and people with DS experience more co‐morbidities and have poorer health outcomes compared to the general population. An area that is not well understood is how patients with DS transition from pediatric to adult care, as well as the details, barriers, and difficulties of these transitions for patients. Hence, we aimed to provide a scoping review of the literature in PubMed, Scopus, and CINAHL on the topic of healthcare transitions (HCTs) for patients with DS. Findings suggest patients with DS who continued receiving care as an adult from a pediatric care provider tended to experience co‐morbidities and other adverse health issues at higher rates than those who entirely switch to an adult‐care team. Patients with DS were unable to undergo transition due to multiple barriers, such as low income, limited/public insurance, gender, and race. We propose potential steps for transition, which focus on ensuring early planning, communicating better, coordinating services, assessing decision‐making capacity, and providing ongoing social and financial support. Future research must further identify and address barriers to HCTs for people with DS.